Ecosystem Service of Shade Trees on Nutrient Cycling and Productivity of Coffee Agro-ecosystems - Rusdi Evizal; Tohari Tohari; Irfan D. Prijambada; Jaka Widada; Donny Widianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2009)
Shade trees are significant in certification scheme of sustainable coffee production. They play an importance role on ecosystem functioning. This research is aimed to study ecosystem service of shade trees in some coffee agro-ecosystems particularly on nutrient cycling and land productivity. Four agro-ecosys tems of Robusta coffee (Coffea canephora), namely sun coffee (without shade trees), coffee shaded by Michelia champaca, coffee shaded by Gliricidia sepium, and coffee shaded by Erythrina indica are evaluated during 2007—2008. Smallholder coffee plantation in Sumberjaya Subdistrict, West Lampung, which managed under local standard were employed using Randomized Complete Block Design with 3 replications. The result showed that litter fall dynamic from shade trees and from coffee trees was influenced by rainfall. Shade trees decreased weed biomass while increased litter fall production. In dry season, shade trees decreased litter fall from coffee shaded by M. champaca. G. sepium and E. indica shaded coffee showed higher yield than sun coffee and M. champaca shaded coffee. Except for M. champaca shaded coffee, yield had positive correlation (r = 0.99) with litter fall production and had negative correlation (r = —0.82) with weed biomass production. Biomass production (litter fall + weed) of sun coffee and shaded coffee was not significantly different. Litter fall of shade trees had significance on nutrient cycle mainly to balance the lost of nitrogen in coffee bean harvesting.Key Words: Coffea canephora, Michelia champaca, Gliricidia sepium, Erythrina indica, litter production, nutrient cycle, coffee yield.